THE INFLUENCE OF EMPLOYEE BACKGROUND AND INTERNAL SERVICE QUALITY ON EMPLOYEE SATISFACTION: A SAMPLE FROM A VIETNAMESE FOOD AND BEVERAGE SERVICE COMPANY - LINTJE SIEHOYONO (Centre For Tourism Planning and Development, 2006)
The purpose of the study is to examine the extent to which the relationship between the internal service quality (ISQ) and employee satisfaction in a Vietnamese food and beverage service company. Based on the previous studies of Heskett et al, (1997) and Heinhuis et al. (1998), seven sub-measurements of ISQ and three sub-measurements of employee satisfaction are applied in the study. In addition, employee background as personal characteristics is also examined in the relation to employee satisfaction whilst cultural variables are held constant. This formal and descriptive correlational study analyzes data from questionnaire and interview. The results show that there is no significant correlation between employee background (age, education qualification, and length of employment) and employee satisfaction. On the other hand, there is significant correlation between internal service quality and employee satisfaction. Technology job fit, delivering service value, customer response, and supervisory control system are the most important measurements of ISQ, which influence the employee satisfaction.